Implementasi Program “Rumah Aman” Sebagai Upaya Pencegahan Kekerasan Pada Anak - Aisya, Nakhlatul; Selvia, Selvia; Dianty, Annisa; Mardhia Soleha, Annisa; Sofiana, Rina; Kalsum, Ummi (Jurnal Salam Sehat Masyarakat (JSSM), 2025)
Violence against children remains a complex and growing social issue in various regions of Indonesia, including the city of Jambi. Data from the Jambi Province Women's Empowerment and Child Protection Agency for 2023 recorded 381 cases of violence against women and children, while in 2024 there were 246 cases. Of these, children were the dominant victims, with 264 cases in 2023 and 158 cases in 2024. Children aged 7–12 years are vulnerable to violence because they are not yet able to protect themselves from violent acts. The objective of this program is to increase children's knowledge and attitudes in preventing violence through education and interactive games. The methods include socialization, game-based education (role-play, picture guessing, body safety zone, and expression tree), and evaluation using pre-tests and post-tests. The results of the activities showed a significant increase in the average score from 5.62 to 8.54 and in attitudes from 5.45 to 8.04. Children were better able to recognize forms of violence, dare to reject inappropriate treatment, and mention self-protection measures. Similar activities are expected to be developed sustainably in schools and communities to strengthen child protection at the community level. Violence against children remains a complex and growing social issue in various regions of Indonesia, including the city of Jambi. Data from the Jambi Province Women's Empowerment and Child Protection Agency for 2023 recorded 381 cases of violence against women and children, while in 2024 there were 246 cases. Of these, children were the dominant victims, with 264 cases in 2023 and 158 cases in 2024. Children aged 7–12 years are vulnerable to violence because they are not yet able to protect themselves from violent acts. The objective of this program is to increase children's knowledge and attitudes in preventing violence through education and interactive games. The methods include socialization, game-based education (role-play, picture guessing, body safety zone, and expression tree), and evaluation using pre-tests and post-tests. The results of the activities showed a significant increase in the average score from 5.62 to 8.54 and in attitudes from 5.45 to 8.04. Children were better able to recognize forms of violence, dare to reject inappropriate treatment, and mention self-protection measures. Similar activities are expected to be developed sustainably in schools and communities to strengthen child protection at the community level.